As the dust settles...n; Never too young to learn; A tribute to Mang Cesar [videorecording] - Lazaro, Cheche (The Probe team, 1994)
Summary: Deals with the re-evaluation of movie industry after the Manila Filmfest scandal; the alleged distribution of "pornographic cartoons" for sex education classes in the elementary and high school levels and the national artist, Cesar Legaspi.